The Working Woman’s ‘Time Poverty’ in the Polders - International Rice Research Institute (International Rice Research Institute, 2022)
In the polders, women often provide unpaid labor in their agricultural activities. They are heavily involved in crop production, homestead gardening, gher operations, as well as livestock and poultry raising. However, the trend is changing; the number of women working in paid jobs in the polders is increasing.